Clinical Features related to human herpesvirus type 6, including aspects of the infecnon in acquired immunodeficiency syndrome - Vianna, Renata A.O.; Pereira, Sabrina B.; Rocha, Anna L.C.; Pereira, Antonio C.M.; Oliveira, Solange A. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Human herpcsvirus-6 (HHV-6) was fírsl isolaled in 1986 frorn patienls with lymphoproliferative diseases. Further studies have shown that HHV-6 is widespread throughout human populalions and that primary infection usually occurs in the First years of life. sometimes causing a benign childhood disease known as exanthcm subitum. In ihis review, lhe syndromes related to HHV-6 and lhe infection in immunocompromised hosts. including the acquired immunodeficiency syndrome, aredescribed.